Brainhack: a collaborative workshop for the open neuroscience community. Issue 1 (December 2016) - Cameron Craddock, R.; S. Margulies, Daniel; Bellec, Pierre; Nolan Nichols, B.; Alcauter, Sarael; A. Barrios, Fernando; Burnod, Yves; J. Cannistraci, Christopher; Cohen-Adad, Julien; De Leener, Benjamin; Dery, Sebastien; Downar, Jonathan; et al.
Abstract Brainhack events offer a novel workshop format with participant-generated content that caters to the rapidly growing open neuroscience community. Including components from hackathons and unconferences, as well as parallel educational sessions, Brainhack fosters novel collaborations around the interests of its attendees. Here we provide an overview of its structure, past events, and example projects. Additionally, we outline current innovations such as regional events and post-conference publications. Through introducing Brainhack to the wider neuroscience community, we hope to provide a unique conference format that promotes the features of collaborative, open science.